CSF Glucose in Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effects of convulsion and fever on the CSF and blood glucose concentrations in febrile and non-febrile children, with and without convulsions, have been studied at the Department of Paediatrics, Kuopio University Hospital and Department of Pharmacology and Toxicology, University of Kuopia, Kuopio, Finland.